Bhandasar Temple at the centre of the Complex - Temples of India Project Team (Jio Institute, 2024)
View of the entire elevation of the Bhandasar Temple from the southwest corner of the complex. The temple proper is painted in bi-chrome, red ochre and white, but the shikhara (superstructure) of the temple is only in white. The plinth of the temple looks like it was built in brick. However, the entire structural core is built in stone. The base of the shikhara has balconies on two terrace levels of the temple. These can be accessed from inside the temple. It is said that one can see the entire Bikaner city from these balconies.